Drei Fälschungen von Papsturkunden des 13. Jahrhunderts - Acht, Peter (Archivio paleografico italiano. Bollettino, 1957)
Keywords: steingaden

De abdij Mariënweerd - Beaufort, René François Paul de (Gelre. Bijdragen en mededelingen van Gelre. Vereeniging tot Beoefening van Geldersche Geschiedenis, Oudheidkunde en Recht, 1957)
Keywords: mariënweerd

Die Basilika von Ilbenstadt. Kurzer Führer durch Kirche und Kloster - Bewerunge, Norbert (Bindernagel, 1957)
Keywords: ilbenstadt

Thibaud, Septième Abbé de Saint-André-au-Bois - Brouette, Émile (Bulletin trimestriel de la Société Academique des Antiquaires de la Morinie, 1957)
Keywords: saint-andré-au-bois

L'abbaye de Belle-Étoile - Cautru, Camille (Art de Basse-Normandie, 1957)
Keywords: belle-étoile

Disquisitio historico-juridica de visitatoribus in Ordine Praemonstratensi - Clerck, D. de (Analecta Praemonstratensia, 1957)
Keywords: ⚖️ chapters and statutes

Les curés blancs - Cluny, Roland (A. Fayard, 1957)
Keywords: 📚 premonstratensian (general)

The Registrum Premonstratense: a lost MS rediscovered - Colvin, Howard M. (Journal of Ecclesiastical History, 1957)
Keywords: 📚 premonstratensian (general)

Anselm von Havelberg. Untersuchungen zur Kirchen- und Geistesgeschichte des 12. Jahrhunderts - Fina, Kurt (Analecta Praemonstratensia, 1957)
Keywords: 👤 anselm of havelberg

Gottfried von Beselich. Untersuchungen über die Anfänge der Klöster Altenberg, Walsdorf und Beselich - Gensicke, Hellmuth (Nassauische Annalen, 1957)
Keywords: altenberg; beselich

De watermolens van Venbergen en andere molens van de Abdij Postel - Groot, I. de (Analecta Praemonstratensia, 1957)
Keywords: postel

Die geistige und religiöse Welt einer Eifel-Abtei im Hochmittelalter. Eine Quelle zur Frömmigkeitsgeschichte der Steinfelder Prämonstratenser - Hegel, Eduard (Trierer Theologische Zeitschrift, 1957)
Keywords: steinfeld

L'Abbaye de Leffe et ses cures avant la Révolution - Jacques, François (Abbaye de Leffe, 1957)
Keywords: leffe

L'archidiaconé d'exception de l'abbaye de Leffe et les cures à la collation de son abbé - Jacques, François (Analecta Praemonstratensia, 1957)
Keywords: leffe

A propos du cérémonial de la vêture dans l'Ordre de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1957)
Keywords: 📚 premonstratensian (general)

L'office et la messe de sainte Madeleine dans le rit de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1957)
Keywords: 🛐 liturgy

La liturgie de Prémontré: Histoire, formulaire, chant et cérémonial - Lefèvre, Placide (Impr. E. Warny, 1957)
Keywords: 🛐 liturgy

Un collectaire de l'abbaye de Grimbergen du début du XVe siècle - Lefèvre, Placide (Analecta Praemonstratensia, 1957)
Keywords: grimbergen; 🛐 liturgy

The Praemonstratensian Canons in the Renaissance Century - Mahoney, John F. (Analecta Praemonstratensia, 1957)
Keywords: 📚 premonstratensian (general)

Románská stavební huť v Doksanech. II. Dílo a působení doksanské huti - Merhautová-Livorová, Anežka (Umění : časopis Ústavu pro theorii a dějiny umění Československé akademie věd, 1957)
Keywords: doksany

Die Prämonstratenser-Klosterkirchen Arnstein, Beselich und Brunnenburg. Ein Beitrag zur Baukunst des Prämonstratenser-Ordens im 12. und frühen 13. Jahrhundert - Miedel, Hilde (Archiv für mittelrheinische Kirchengeschichte, 1957)
Keywords: arnstein; beselich; brunnenburg

Abt Dominikus von Lieblein, der größte Abt des Klosters Speinshart - Motyka, Gustl (Die Oberpfalz, Heimatzeitschrift für den ehemaligen Bayerischen Nordgau, 1957)
Keywords: speinshart

Klostret i den stilla dalen - Niklasson, Nils (Vikarfvet, 1957)
Keywords: dragsmark

Adatok a magyarországi premontreiek Árpád-kori történetéhez - Oszvald, Arisztid (Művészettörténeti Értesítő, 1957)
Data on the history of the Hungarian Premontreians in the Árpádian period
Keywords: 🇭🇺 hungary (general)

Basilika und Prämonstratenserabtei Geras: Stifts- u. Pfarrkirche Mariä Geburt - Pfiffig, Ambros Josef (1957)
Keywords: geras

Heiligerlee - R.O.B., Amersfoort (Bulletin KNOB, 1957)
Keywords: heiligerlee

Románská stavební huť v Doksanech. I. architektura okruhu kláštera doksanského - Radová-Štiková, Milada (Umění : časopis Ústavu pro theorii a dějiny umění Československé akademie věd, 1957)
Keywords: doksany

Torre Abbey, Torquay - Ralegh Radford, C. A. (The Archaeological Journal, 1957)
Keywords: torre

Mülheimer Beziehungen zur Abtei Hamborn, insbesondere Beiträge zur Geschichte des Kolkerhofes - Rommel, Franz (Duisburger Forschungen, 1957)
Keywords: hamborn

L'Abbadia premonstratense di San Samuele in Barletta - Santeramo, Salvatore (Analecta Praemonstratensia, 1957)
Keywords: barletta

Wreck rolls of Leiston Abbey - Schofield, B. (Studies Presented to Sir Hilary Jenkinson, 1957)
Keywords: leiston

Das Obleibuch des Klosters Schäftersheim vom Jahre 1393 - Schumm, Karl (Württembergisch Franken, 1957)
Keywords: schäftersheim

L'église de Blanzey - Simonin, Pierre (Le pays lorrain, 1957)
Keywords: blanzey

Das älteste Kopialbuch des Stiftes Wilten - Steinegger, Fritz (Tiroler Heimat, 1957)
Keywords: wilten

Petrus de Lutra - Valvekens, J.B. (Analecta Praemonstratensia, 1957)
Keywords: kaiserslautern

Acta et Documenta loannis de Pruetis, abbatis Praemonstratensis - Valvekens, Johannes B. (Analecta Praemonstratensia, 1957)
Keywords: prémontré

Haereses ac Sectae ineuntis Medii Aevi et Praemonstratenses - Valvekens, Johannes B. (Analecta Praemonstratensia, 1957)
Keywords: 📚 premonstratensian (general)

Petrus de Lutra - Valvekens, Johannes B. (Analecta Praemonstratensia, 1957)
Keywords: 📚 premonstratensian (general)

De Sint-Michielsabdij in de sagenschat van de Polders ten noorden van Antwerpen - Van den Berg, M. (Analecta Praemonstratensia, 1957)
Keywords: antwerp

The estates of Titchfield Abbey, c. 1245 to c. 1380 - Watts, D. G. (University of Oxford, 1957)
Keywords: titchfield

Die Urkunden und Urbare des Klosters Schäftlarn - Weissthanner, Alois (C.H. Beck, 1957)
Keywords: schäftlarn